Immunohistochemical parameters of CD56 in guinea pigs’ lung in the dynamics of the experimental allergic inflammation - Popko, S. S.; Yevtushenko, V. M.; Попко, Світлана Сергіївна; Євтушенко, Валентина Михайлівна (My University, 2021)
Aim of the study: The aim of this work is to study morphometric characteristic and distribution of CD56 positive cells in guinea pigs’ lung in the dynamics of the experimental allergic inflammation.
Keywords: тези доповідей